Anisotropic transport properties of tetragonal SrFeO2.84 single crystal. (September 2020) - Xu, Haohang; Liu, Qingyuan; Zhou, Xuebo; Tao, Lei; Huo, Mingxue; Wang, Xianjie; Sui, Yu
Abstract: The tetragonal SrFeO2.84 single crystal was grown by using floating zone method, and followed by resistivity and magnetization measurements with respect to temperature. Here, the magnetization data shows an antiferromagnetic ordering below 63 K, accompanied by the formation of the charge ordering. However, an anomalous insulator to metal transition occurs below 40 K in the basal plane of SrFeO2.84 single crystal, while the resistivity along the c axis still keeps insulating. Our results reveal that, the anisotropy of resistivity in SrFeO2.84 is caused by the magnetically driven orbital-selective Mott phase transition. Highlights: The tetragonal SrFeO2.84 single crystal was grown by using floating zone method. We found that SrFeO2.84 crystal shows an obvious anisotropy of resistivity in the basal plane and along c axis. The insulator-metal transition appeared in SrFeO2.84 is caused by magnetically driven orbital-selective Mott transition.